FAKTOR-FAKTOR YANG DIPERTIMBANGKAN KONSUMEN MENGGUNAKAN MEDIA SOSIAL WHATSAPP DI KOTA PALU - Adiana, Dewa Made; Wahyuningsih, Wahyuningsih; Sutomo, Maskuri (Katalogis, 2018)
The objective of the research is to find out the factors that are considered by consumers in using whatsapp social media in Palu City. The number of samples in is 95 respondents. The techniques of data are interviews, questionnaires, and documentation. The research method uses a purposive sampling technique; besides the measurement scale of the research is a factor analysis. The result of the research is formed 4 factors that are considered by consumers in using whatsapp social media in Palu City, namely the factor of Service features, Cost, Security and Social.